THE BIOLOGICAL CYCLE OF SUNFLOWER BROOMRAPE - DUCA Maria (Journal of Plant Development, 2013)
Orobanchaceae is a dicot family, which consists of annual and perennial plants distributing from tropical to subarctic regions, predominately in temperate regions. Broomrape (Orobanche cumana Wallr. = Orobanche cernua Loefl.) is a parasitic angiosperm that has been causing a great deal of damage to sunflower production in many countries, including Republic of Moldova. This parasitic angiosperm depends entirely on the host for its supply of water and nutrients. A thorough understanding of its biology, including detailed knowledge of the specific mechanisms of parasitism, is needed in order to develop novel control methods. Some main developmental steps are described for the root parasites: seed conditioning and germination, haustorium formation, penetration into host tissues, maturation of the parasite plant, and seed production. All these stages were studied in artificial and natural conditions.